О ПОТЕНЦИАЛЬНОЙ АЛМАЗОНОСНОСТИ ГРАНАТОВЫХ АМФИБОЛИТОВ П-ОВА КАМЧАТСКИЙ МЫС (ВОСТОЧНАЯ КАМЧАТКА) - Сидоров Е.Г.; Осипенко А.Б.; Козлов А.П.; Рудашевский Н.С.; Пилипюк А.Н. (My University, 2006)
New data on chemistry of the indicative rock-forming minerals were obtained for garnet, clinopyroxene and ilmenite from garnet amphibolites in Cretaceous ophiolite complex of the Kamchatsky Mys Peninsula (Eastern Kamchatka). Under concept of potential diamond-bearing of amphibolites of the Later-Mesozois ophiolitic complex, represented in placers around Soldatsky peridotite massif, chemical composition of minerals and calculated thermodynamic conditions of amphibolite metamorphism were compared with data on typical diamond-bearing associations of different types. Analysis of obtained data has proved the lack of any indications for diamond-bearing parageneses formed in studied metabasites, which were suggested earlier as a source of diamonds or their polymorphs for placers located in peripheral parts of Soldatsky peridotite massif. Assumption of amphibolites as a primary source of diamonds for those placers in the region hasn't any real geological base, some reports on diamonds found in the area need to be approved with the careful diagnostics to carry out.
Keywords: 549.0; Мезозой::Меловая